Transformasi Pembelajaran PKn: Menyelidiki Dampak Model Problem Based Learning terhadap Hasil Belajar Siswa [Transforming Pkn Learning: Investigating the Impact of the Problem-Based Learning Model on Student Learning Outcomes] - Monica, Caroline; Padudung, Frisca Yuyun; Riza, Renzy; Lawado, Saphira Amanda Destrisha (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan, Universitas Pelita Harapan, 2023)
The study aims to evaluate the influence of the use of Problem Based Learning (PBL) on student learning outcomes in the subject of Civic Education. By applying the true experiment method that uses Posttest Only Control as the research design, the research was conducted in high school and involved forty-three students. The test questions play a role as an instrument that measures student learning outcomes, where the test questions are valid, have a low level of reliability, and focus on understanding the material of Civic Education. The results showed that the use of the PBL Model had a significant effect on improving student learning outcomes in the subject of Civic Education, as evidenced by the T test to see the mean of the experimental class (16.09) and the control class (14.54). In addition, this study stated that gender factors did not have a significant effect on student learning outcomes in the subject of Civic Education, in line with the results of the Pearson correlation test of 0.16. The main contribution of this research is to bridge the knowledge gap related to the impact of PBL on learning outcomes, especially in the context of Civic Education subjects and to contribute by focusing on subjects that have curriculum specificity, regarding aspects of Civic Education. With these contributions and objectives, it is hoped that this research will provide valuable insights for education practitioners, teachers, and policy makers in improving the effectiveness of PKn learning in the modern era.